2017
DOI: 10.1155/2017/5498054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anti‐Inflammatory Properties of Isoorientin Isolated from Tubers of Pueraria tuberosa

Abstract: Inflammation is the major causative factor of different diseases such as cardiovascular disease, diabetes, obesity, osteoporosis, rheumatoid arthritis, inflammatory bowel disease, and cancer. Anti-inflammatory drugs are often the first step of treatment in many of these diseases. The present study is aimed at evaluating the anti-inflammatory properties of isoorientin, a selective cyclooxygenase-2 (COX-2) inhibitor isolated from the tubers of Pueraria tuberosa, in vitro on mouse macrophage cell line (RAW 264.7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 22 publications
0
33
0
3
Order By: Relevance
“…According to Xiao et al, orientin suppressed the TNF‐ α , IL‐6, IL‐18, and IL‐1 β production mediated by LPS in RAW 264.7 cells as well as the expression of COX‐2 and i NOS through the inhibition of NF‐ k B pathway. Isoorientin successfully reduced the expression of TNF‐ α , IL‐6, 5‐lipoxygenase (5‐LOX), and IL‐1 β in both LPS stimulated RAW cell and carrageenan induced inflammatory model . For vitexin, isovitexin and schaftoside, though sonicated absolute ethanol and water extracts possessed significant higher concentration, other method prepared extracts showed considerable amount of vitexin, isovitexin and schaftoside too which further supported their location in the positive side of PC2 in the PLS biplot.…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…According to Xiao et al, orientin suppressed the TNF‐ α , IL‐6, IL‐18, and IL‐1 β production mediated by LPS in RAW 264.7 cells as well as the expression of COX‐2 and i NOS through the inhibition of NF‐ k B pathway. Isoorientin successfully reduced the expression of TNF‐ α , IL‐6, 5‐lipoxygenase (5‐LOX), and IL‐1 β in both LPS stimulated RAW cell and carrageenan induced inflammatory model . For vitexin, isovitexin and schaftoside, though sonicated absolute ethanol and water extracts possessed significant higher concentration, other method prepared extracts showed considerable amount of vitexin, isovitexin and schaftoside too which further supported their location in the positive side of PC2 in the PLS biplot.…”
Section: Resultsmentioning
confidence: 58%
“…Isoorientin successfully reduced the expression of TNF-α, IL-6, 5-lipoxygenase (5-LOX), and IL-1β in both LPS stimulated RAW cell and carrageenan induced inflammatory model. 46 For vitexin, isovitexin and schaftoside, though sonicated absolute ethanol and water extracts possessed significant higher concentration, other method prepared extracts showed considerable amount of vitexin, isovitexin and schaftoside too which further supported their location in the positive side of PC2 in the PLS biplot. Isovitexin was the most abundant in sonicated absolute ethanol extract.…”
Section: Figurementioning
confidence: 70%
“…Such limitations have raised interest in expanding research into the use of natural products as therapeutic agents to prevent obesity or its associated complications. Although some studies conducted over the years showed isoorientin, or plants rich in this natural compound, can ameliorate obesity-related complications, such as oxidative stress, inflammation, hyperlipidemia, and insulin resistance [5,[16][17][18][19][20], there is still relatively little information about its impact as a pure compound on obesity.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up study, we isolated isoorientin, a representative flavonoid glycoside, from VBME (Kwon et al, 2016). The anti-inflammatory properties of isoorientin have been attributed to its selective cyclooxygenase-2 inhibitory effects (Anilkumar et al, 2017;Sumalatha et al, 2015).…”
Section: Introductionmentioning
confidence: 99%